Going viral : the 9 secrets of irresistible marketing - Coker, Brent (Pearson, 2016)
Everyone wants their voice to be heard above the noise of other brands. But how do you get your messages to spread far and wide? YOU NEED TO GO VIRAL It's not just down to luck. If you want to make an impact, you need to make your marketing messages magnetic and, in this fascinating book, Brent Coker will show you how. Packed full of practical techniques, expert research and real-life examples, you'll quickly uncover the nine secrets of irresistible marketing that will work whatever the size of your company. Discover the science behind the world's most viral ideas, learn how to create messages.